The determinant factors affecting cloud computing adoption by Small and Medium Enterprises (SMEs) in Sabah, Malaysia - C. Fook Ming; C. Kim On; Rayner Alfred; T. Tse Guan; A. Patricia (Faculty of Electronics and Computer Technology and Engineering, Universiti Teknikal Malaysia Melaka, 2018)
Cloud computing offers organisations many benefits such as low entry costs, enhanced flexibility, ubiquitous access, and scalability. Despite its attractiveness and benefits, Small and Medium Enterprises (SMEs) are still hesitant to adopt cloud computing services. This study used the Technology Organisation Environment (TOE) framework to identify the determinant factors affecting the adoption of cloud computing by SMEs in Sabah, Malaysia. Survey questionnaires collected data from 170 SMEs across all sectors within the region. A total of six factors were verified in this research. The results indicated that cost saving, top management support and technology readiness are the main factors affecting the adoption of cloud computing by SMEs in Sabah. However, other three factors; relative advantage, competitive pressure, and external support did not affect the adoption of cloud computing for these organisations. This finding could provide insight and clarity of information for the SMEs’ decision and policymakers in various sectors. It also provides understanding on the different influencing factors that affect SMEs’ perceptions of the importance of adopting cloud computing.